Individual Prevention Of Drug-Related Crimes - Hladkova, Yevheniia; Hasparian, Serafyma (Archives of Criminology and Forensic Sciences, 2026)
The purpose of the article is to examine tactics of individual prevention and possibilities of their application for dealing with the drug-related crimes. Results of the study allow us to draw several conclusions. Firstly, we differentiate between individual prevention of drug consumption and individual prevention of the drug-related crimes. Secondly, individual prevention is a complex system of measures, including identifying persons who consume drugs, performing control of the lifestyle of said persons and taking measures to prevent them from further drugs abuse. Thirdly, individual prevention involves a wide variety of measures, including visits by the police officer, medical oversight, and pedagogical influence. Actual measures should be chosen according to the situation, personality of the person, nature and gravity of the offences, committed by him or her, information about his or her social connections, etc. Practical implications of the study lie in the recommendations for the activities of the police aimed at ensuring efficient individual prevention of the drug-related crimes. They involve fostering cooperation with the institutions that can provide the police with information about people who partake in drugs abuse, e.g. medical institutions, NGOs, etc. Furthermore, such cooperation is useful to ensure indirect, as well as direct control over their lifestyle, aimed at limiting their connections with the negative microsocium (i.e., drug users and traffickers). Besides those measures, we stress upon the necessity of criminological influence in order to ensure efficient individual prevention, especially towards those who commit drug-related crimes. Value/originality. The paper provides practical pieces of advice for performing individual prevention of the drug-related crimes and drug consumption by the police officers. Additionally, it provides basis for the further research of the issues of drug-related delinquencies prevention.